Proceedings of the 25th ACM International Conference on Multimedia 2017
DOI: 10.1145/3123266.3123365
|View full text |Cite
|
Sign up to set email alerts
|

Region-based Activity Recognition Using Conditional GAN

Abstract: We present a method for activity recognition that first estimates the activity performer’s location and uses it with input data for activity recognition. Existing approaches directly take video frames or entire video for feature extraction and recognition, and treat the classifier as a black box. Our method first locates the activities in each input video frame by generating an activity mask using a conditional generative adversarial network (cGAN). The generated mask is appended to color channels of input ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Maps from Satellite Images [36] super resolving face images [57] Unsupervise classification of street architectures [66] Feature Filter for EEG [74] Photos to Emojis CT Image Augmentation [37] HD movie from low-quality movie [58] Photograp h Editing Region-based Activity Recognition [38] Face Aging…”
Section: Architecture Basedmentioning
confidence: 99%
“…Maps from Satellite Images [36] super resolving face images [57] Unsupervise classification of street architectures [66] Feature Filter for EEG [74] Photos to Emojis CT Image Augmentation [37] HD movie from low-quality movie [58] Photograp h Editing Region-based Activity Recognition [38] Face Aging…”
Section: Architecture Basedmentioning
confidence: 99%
“…While a binary map that exactly pinpoints the location of classdiscriminative features in the input is the most desirable and has been found to improve classification performance [28], such accurate maps require human-in-the-loop processing and cannot be readily available for most datasets. Our strategy also differs from feature muting [29] that sets a fixed number of features to zero, which can drastically change sample statistics and risk muting useful features through the fixed threshold.…”
Section: Masking Superficial Observationsmentioning
confidence: 99%
“…Therefore, conditional GAN can be seen as an improvement in transforming unsupervised GAN into a supervised model. Later quantities of experiments showed that this method was very effective [16]- [18].…”
Section: B Conditional Generative Adversarial Networkmentioning
confidence: 99%